EU POLICY TOWARDS MACEDONIA DURING THE YUGOSLAV CRISIS - Marolov, Dejan (European Scientific Journal, ESJ, 2014)
The EU19 policy and its relation to the process of disintegration of the Yugoslav federation has been featured quite a lot. However, within these general EU policy toward the Yugoslavian problem there was an, more or less, individual policy toward each constitutive republics of Yugoslavia. That is exactly the matter that will be dealt in this paper. In this way we will try to present the specific EU policy towards Macedonia as one of the six constitutive republics of the former Yugoslav federation for the period of the duration of the Yugoslav crisis. The logical question here is what exactly we mean by the term "Yugoslav crisis" and precisely what time framework we are talking about. At this point we are not going to specify the exact dates but we are going simply to suggest that "Yugoslav crisis" is a few months period before the declaration of independence by Slovenia and Croatia, including the military actions in these two republics, until the Dayton Peace Agreement for B&H. After this there was a period of stagnation and relatively peaceful conditions in the territory of former Yugoslavia, but only until 1999, when a military conflict broke out in the so-called "southern front” in Kosovo and later in 2001 in Macedonia. However, the conflicts in Kosovo and Macedonia can not be included in the term , Yugoslav crisis”, because of the fact that at that time Yugoslavia did not exist anymore and that these military conflicts occurred in two different sovereign and mutually recognized states20. So, in this paper we will try to highlight the most important elements of EU policy towards Macedonia during the Yugoslav crisis and the question which influences this policy had on the newly independent Republic.